Implications of Negative Interest Rate Policy on Emerging Markets and Developing Economies - Víchová, Markéta; Brůna, Karel, 1973-; Szabo, Milan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
This paper is focused on effects of negative interest rate policy of central banks in advanced economies on emerging market and developing countries. It has been argued that asset prices in developing economies financial markets are influenced more by the monetary policies of the advanced economies rather than by their own policies and fundamentals. Spillover effect are mostly similar to those of other unconventional monetary policy measures and it is hard to differentiate them as they were implemented together at the same time. This paper examines gross financial flows between the countries exposed to negative interest rates and developing countries. Financial flows were led by the motivation of investors who lost their profit opportunities in domestic markets and trying to search for new profit opportunities in emerging markets. This may harm financial stability of emerging markets.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses